Application of the Traditional Dakon Game in Second Grade Elementary School Multiplication Operation Material - Asmawati, Siti Nor; Sari, Arissona Diyah Indah (PUSAKA: Journal of Educational Review, 2024)
Mathematics lessons are one of the subjects that are quite unpopular for students, in fact many students assume that mathematics lessons are very difficult, which is a reason for some students which ultimately affects the interaction of the teaching and learning process. Apart from these problems, the lack of learning resources and limited media or teaching aids is one of the causes that results in learning being more one-way and boring, which has an impact on reducing student learning outcomes. Learning media that can be applied in elementary schools as a solution to improve student learning outcomes is the use of dakon media. The aim of this research is to apply the dakon game media to introduce the basic concepts of multiplication calculation operations which are very important for students.